Pengawasan dan Pengendalian Kegiatan Bantuan Stimulan Perumahan Swadaya Kementerian PUPR Tahun 2017 di Provinsi Kalimantan Barat - Ratih Setyo Rini (Universitas Bina Sarana Informatika, 2018)
The Government has conducted variety efforts to address the needs and problems of housing, among other things through the Self-help Housing Stimulant Assistance Program (known by its Indonesian acronym BSPS). BSPS encourage the community to be able to build the House or re-improvement the house being livable. Regional Management Consultant known KMW is responsible as supervisors so that the implementation of the activities of the BSPS in accordance with quantitative and also kuaitatif target. This research is qualitative research conducted from March to December 2017 in West Kalimantan province. The data is obtained through a written report or an interview directly with the all parties involved in activities of the BSPS in West Kalimantan. The research found that monitoring and control functions has encouraged the activities of the BSPS in West Kalimantan was completed on time and get the House habitable as expected. Nevertheless some recommendations are made for improvements to the implementation of the activities as well as the monitoring process in the coming year.